Adaptive Gradient Compression: An Information-Theoretic Analysis of Entropy and Fisher-Based Learning Dynamics - Hidayaturrahman Hidayaturrahman (International Journal of Computer Science and Humanitarian AI, 2025)
Deep neural networks require intensive computation and communication due to the large volume of gradient updates exchanged during training. This paper investigates Adaptive Gradient Compression (AGC), an information-theoretic framework that reduces redundant gradients while preserving learning stability. Two independent compression mechanisms are analyzed: an entropy-based scheme, which filters gradients with low informational uncertainty, and a Fisher-based scheme, which prunes gradients with low sensitivity to the loss curvature. Both approaches are evaluated on the CIFAR-10 dataset using a ResNet-18 model under identical hyperparameter settings. Results show that entropy-guided compression achieves a 33.8× reduction in gradient density with only a 4.4% decrease in test accuracy, while Fisher-based compression attains 14.3× reduction and smoother convergence behavior. Despite modest increases in per-iteration latency, both methods maintain stable training and demonstrate that gradient redundancy can be systematically controlled through information metrics. These findings highlight a new pathway toward information-aware optimization, where learning efficiency is governed by the informational relevance of gradients rather than their magnitude alone. Furthermore, this study emphasizes the practical significance of integrating information theory into deep learning optimization. By selectively transmitting gradients that carry higher information content, AGC effectively mitigates communication bottlenecks in distributed training environments. Experimental analyses further reveal that adaptive compression dynamically adjusts to training dynamics, providing robustness across various learning stages. The proposed framework can thus serve as a foundation for developing future low-overhead optimization methods that balance accuracy, stability, and efficiency, and crucial aspects for large-scale deep learning deployments in edge and cloud computing contexts.